The identity and occurrence of Phyllanthus hookeri Muell.-Arg. and P. nozeranii Rossignol & Haicour (Euphorbiaceae) in India - Raju, Vatsavaya S.; Suthari, S.; Ragan, A. (Bangladesh Journal of Plant Taxonomy, 2011)
There are 16 species of Phyllanthus subgenus Phyllanthus reported from India. The present paper adds two more species that are invasive weeds in the paddy fields and on forest floors, namely Phyllanthus hookeri Muell.-Arg. and P. nozeranii Rossignol & Haicour of sect. Urinaria subsect. Urinaria of Phyllanthus. The former is somewhat woody and perennial whereas the latter is slender and monsoonal. The presence of these two taxa in India was brought to light in 1987 by Rossignol et al. based on the herbarium specimens collected earlier to 1863 and deposited at Paris from northeastern and southeastern India. Whilst Phyllanthus hookeri is overlooked or underrated by the taxonomists, P. nozeranii is misidentified and considered conspecific with P. urinaria L. Keywords: Phyllanthus urinaria complex; P. hookeri; P. nozeranii; Identity; Chemotaxonomy; India. DOI: 10.3329/bjpt.v18i1.7839 Bangladesh J. Plant Taxon. 18(1): 57-63, 2011 (June)